PENGARUH KOMPETENSI, LOCUS OF CONTROL, DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI (STUDI PADA PENGADILAN TATA USAHA NEGARA SEMARANG) - Danny Agus Prabowo, 13.05.51.0177; Rahayuningsih, Sri (Students' Journal of Economic and Management, 2019)
This research aims to examine and analyze the influence of competencies, locus of control, and career development on employee performance. The object of research in this paper is the employee of the Semarang State Administrative Court. The sampling technique in this research use the census method by 65 respondents. Analysis of the data used includes validity test with KMO (Kaiser Meyer Olkin), reliability test with Alpha Cronbach, multiple regression analysis, model test with Adjusted R square and f test, t test to test and prove research hypothesis. The results of the research are: (1) Competence has a positive and significant effect on employee performance. (2) Locus of control has a positive and significant effect on employee performance. (3) Career development has a positive and significant effect on employee performance. Keywords :Competence, locus of control, career development and employee performance